The Effect of Using Duolingo Application towards Students’ Grammar Mastery in Simple Present Tense - Ade Sudirman; Tatu Munawaroh; Ikah Fatmawati (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2023)
The purpose of this research to determine the effect of using Duolingo application towards students’ grammar mastery in simple present tense at the seventh grade students of MTS Miftahul Afkar in academic year 2021-2022. This research used a quantitative approach, especially a quasi-experimental method with pre-test and post-test for collecting the data. Duolingo application used as learning media to improve students’ grammar mastery especially in simple present tense. In this research, the researcher used two classes with total population of 58 students. The result of this research was calculated using the T-test. The result in the experimental class showed that the average post-test score (73,9) was bigger than the pre-test score (57,2) while the result in the control class showed that the average post-test score (67,1) was bigger than the pre-test score (57,2). By using the t-test, the result showed that the value of Ttable (1,673) was bigger than Tcount (-20,112) with a significant level of 0,05. This result indicated that Ho was rejected and Ha was accepted. This findings indicated that the Duolingo application has a significant effect towards students' grammar mastery at the seventh grade students of MTS Miftahul Afkar in academic year 2021-2022.